Bulk rock carbon- and oxygen-isotope ratios, calcium carbonate content, magnetic susceptibility and clay mineral assemblages from the Vergol-Morénas composite section from the Valanginian Stage, Vocontian Basin, SE France - Martinez, Mathieu; Guillois, Landry; Boulvais, Philippe; Deconinck, Jean-François (PANGAEA, 2019)
These contain bulk-rock carbon and oxygen isotope ratios, CaCO3 content, magnetic susceptibility values and clay mineral assemblages from the Valanginian part of the Vergol-Morénas composite section, SE France. Two sequences have been analysed in this study. The lower sequence (Sequence 1 or S1) was analysed at the transition between the Pertransiens and the Campylotoxus zones. The sequence is located in the Vergol section. The upper sequence (Sequence 2 or S2) is located within the Verrucosum Zone and is located in the Morénas section. The data were measured from January 2018 to November 2019 at the Université de Rennes 1 and the Université de Bourgogne Franche-Comté.
Keywords: CaCO3 content; Clay minerals; Cretaceous; Magnetic susceptibility; Stable isotopes; Vocontian Basin